Electrophysiological correlates of attentional monitoring during a complex driving simulation task - Gianfranchi, Evelyn; Mento, Giovanni; Duma, Gian Marco; Chierchia, Christian; Sarlo, Michela; Tagliabue, Mariaelena (Biological psychology, 2020)
•Lots of cognitive resources are employed in complex tasks such as driving.•The oddball paradigm can be employed as an index of available attentional resources.•Subjects drove a simulator during a passive auditory multi-feature oddball task.•Learning to drive safely leads to larger amplitudes in early ERP components.•Traffic-related sounds elicit higher P3a amplitude than other tones. Starting from the evidence that complex tasks (e.g., driving) require lots of cognitive resources, this research aims at assessing the change of attentional electrophysiological correlates during an oddball task performed while driving a simulator. Twenty-four participants drove along six courses on a moped simulator, preceded by a baseline condition (i.e., watching a video clip of one driving course). Throughout the task, an auditory passive multi-feature oddball with both traffic-related and unrelated stimuli was presented, and the EEG activity was recorded along with driving performance indexes. The main results point out that, as participants learn to drive safely, more attentional resources are available to process the deviant oddball stimuli, as shown by the increase in the amplitude of mismatch negativity (deviant pure tones) and P3a (traffic-related sounds) in the second block of driving. We interpreted these effects as dependent on stimuli complexity and salience.